PROSES TERBENTUKNYA DESA BLIMBINGSARI SEBAGAI DESA WISATA BERBASIS MASYARAKAT - Ni Wayan Sri Rahayu (UHN IGB Sugriwa Denpasar, 2022)
This study discusses Blimbingsari Tourism Village, which talks in more detail about the process of forming Blimbingsari Village as a community-based tourism village. This research is a type of qualitative research using a historical approach to the rural economy. The theory used in this research is Pieere Bourdieu's Generative Structural theory. The results of the study, namely the formation of Blimbingsari Village as a Tourism Village were motivated by several factors such as the thoughts of several Blimbingsari Village leaders who had the initiative to form Blimbingsari Village as a Tourism Village. Blimbingsari Village is the only village in Bali that has a community adhering to the Protestant Christian belief with a very thick Balinese culture. This can be seen from the existence of the church which has a building structure resembling a temple building and the use of traditional Balinese clothing and facilities during contextual worship. In addition, the Bali Bombing incident which had a bad impact on the tourism sector was also a strong factor in the formation of Blimbingsari Village as a Tourism Village. Various efforts have been made by the people of Blimbingsari Village to realize Blimbingsari Village as a Tourism Village, including forming a tourism committee and establishing cooperation with various universities both National and International